CONCEPTUAL SUPPORT FOR PUBLIC MANAGEMENT OF SUSTAINABLE REGIONAL DEVELOPMENT - Panova, Tetyana (Public Management and Policy, 2025)
Sustainable regional development in modern public management is becoming increasingly relevant and poses global challenges. The article discusses conceptual approaches to ensuring public management of sustainable regional development in the context of modern challenges. The most attention is paid to multilevel governance, e-government, and public administration. A separate important process that affects the overall effectiveness of administration at all levels in terms of sustainable development is the cooperation of citizens and civil society institutions and their significant contribution to the processes of regional improvement. The relevance of the topic is determined by the need to move from fragmented management decisions to a systemic management model that combines economic, social, and environmental development goals. In the context of global challenges, military threats, and socio-economic instability, the issue of developing effective conceptual approaches to regional development management is of particular importance. The purpose of the article is to define the theoretical and methodological foundations and principles of conceptual support for public management of sustainable regional development. To comprehensively study the issue and all the interrelationships in the system, methods such as systemic, structural-functional, and comparative approaches were used. It has been determined that in the context of the incomplete implementation of decentralization reform due to the outbreak of hostilities in 2022, it is particularly important to increase the capacity of local communities, expand their powers, and strengthen the role of public administration bodies in meeting the needs of citizens. It has been proven that these concepts form the basis for further changes in the public administration system through the sustainable development of regions, particularly in the post-war period, when issues of restoration and ensuring sustainable development of territories become relevant.